Faktor Predisposisi, Klasifikasi Subgrup, Biomarker dan Mekanisme Pencegahan Obesitas : Tinjauan Pustaka - Mira Andini; Budirman Budirman; Besse Uswatun Hasanah (Direktorat Politeknik Kesehatan Makassar, 2025)
Obesity has emerged as a critical global public health challenge, driven by multifactorial predisposing elements such as sociodemographics, behavior, genetics, and obesogenic environmental factors. This systematic literature review synthesizes evidence on obesity subgroups (e.g., metabolically healthy obesity [MHO], metabolically unhealthy obesity [MUO]), biomarkers (microRNA, adipokines, oxidative stress markers, gut microbiota, and lipid accumulation product index), and prevention strategies. A systematic search of the PubMed, Scopus, and Web of Science databases (2010–2023) identified peer-reviewed studies addressing the etiology, classification, and interventions for obesity. Key findings highlight the interaction between early-life nutritional deficiencies and subsequent metabolic dysregulation, the role of visceral adipose tissue (VAT) in refining the obesity phenotype, and the diagnostic potential of biomarkers such as miR-222 and leptin. Prevention strategies, including school-based nutrition education, taxes on ultra-processed foods, and bariatric surgery for severe cases, demonstrate varying efficacy across populations. This review emphasizes the need for a multidimensional approach tailored to regional contexts, particularly in low- and middle-income countries where the dual burden of malnutrition persists. By integrating evidence of genetic-environmental interactions and new biomarkers, this research provides actionable insights for policymakers and health practitioners to reduce the growing burden of obesity. Keywords: predisposing factors, subgroup classification, biomarkers, prevention mechanisms, obesity